2007
DOI: 10.1086/520925
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeObservations of Chromospheres in Metal-Deficient Field Giants

Abstract: Hubble Space Telescope high-resolution spectra of metal-deficient field giants more than double the stars in previous studies, span $3 mag on the red giant branch, and sample an abundance range ½Fe/H ¼ À1 to À3. These stars, in spite of their age and low metallicity, possess chromospheric fluxes of Mg ii (k2800) that are within a factor of 4 of Population I stars, and they give signs of a dependence on the metal abundance at the lowest metallicities. The Mg ii k line widths depend on luminosity and correlate w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…Mass flows can produce asymmetric profiles of Hα and Na D, as well as emission asymmetries and velocity shifts in the reversed absorption core of Ca ii and Mg ii. These features have been measured in red giants in many globular clusters (Cacciari et al 2004;McDonald & van Loon 2007;Mészáros et al 2008Mészáros et al , 2009b and in metal-poor field stars (Smith & Dupree 1988;Dupree & Smith 1995;Dupree et al 2007). However, the velocities inferred from the optical profiles are generally less than the escape velocity from the star, and cannot truly be identified as stellar winds.…”
Section: Spectroscopic Diagnostics Of Windsmentioning
confidence: 79%
See 2 more Smart Citations
“…Mass flows can produce asymmetric profiles of Hα and Na D, as well as emission asymmetries and velocity shifts in the reversed absorption core of Ca ii and Mg ii. These features have been measured in red giants in many globular clusters (Cacciari et al 2004;McDonald & van Loon 2007;Mészáros et al 2008Mészáros et al , 2009b and in metal-poor field stars (Smith & Dupree 1988;Dupree & Smith 1995;Dupree et al 2007). However, the velocities inferred from the optical profiles are generally less than the escape velocity from the star, and cannot truly be identified as stellar winds.…”
Section: Spectroscopic Diagnostics Of Windsmentioning
confidence: 79%
“…There are no X-ray sources at the positions of the two stars with strongest He absorption in the HEASARC Archives (http://heasarc.gsfc.nasa.gov), indicating that X-ray illumination does not appear to be present to strengthen the line. The RHB star, BD +17 • 3248, has a chromosphere as documented also by the presence of Mg ii ultraviolet emission (Dupree et al 2007). (Dupree et al 1992a;Smith et al 2004) have been added to this figure (see Table 3 The star HD 195636 displays an exceptionally strong He line.…”
Section: Equivalent Widthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-mass stars in galactic globular clusters lose ∼20% of their mass during the ascent of the first red giant branch (RGB; Dupree et al 2007;Origlia et al 2007;McDonald & van Loon 2007), offering a partial explanation for the blue extent of the core-helium-burning horizontal branch (Rood 1973). It has been argued recently that in the old (8 Gyr), supersolar-metallicity ( ), massive open cluster NGC 6791, at least Z Ӎ 0.05 40% of RGB stars experience higher rates of mass loss; this would lead to their departure from the RGB before the helium flash, resulting in undermassive helium white dwarfs (Castellani & Castellani 1993;Hansen 2005;Kalirai et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies by Schrijver (1987) and Rutten et al (1991) have not identified a metallicity effect on chromospheric emission, particularly Ca II and Mg II, especially in main-sequence stars. On the other hand, more recent observations by the Hubble Space Telescope concerning chromospheric Mg II fluxes given by Dupree, Li & Smith (2007) indicate signs of dependence on metallicity at the lowest metallicities, although these results were obtained for giants rather than dwarfs.…”
Section: Comparison To Observational Datamentioning
confidence: 76%